Revitalizing Rural Development: Exploring Innovations in BUMDES Initiatives: Revitalisasi Pembangunan Pedesaan: Menjelajahi Inovasi dalam Inisiatif BUMDES - Agustian, Yonki; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the challenges faced by the local government in Banjarwungu city concerning its support for BUMDes, as evidenced by inadequate infrastructure, intermittent connectivity issues, and a lack of local understanding regarding BUMDES. The research aims to dissect and capture the progress of BUMDES, addressing the local issues in Banjarwungu, Tarik-Sidoarjo. Employing an exploratory and subjective methodology, data were gathered through interviews, observations, and documentation from key informants including the BUMDES executive director and community members. The findings reveal successful BUMDES development aligning with goals and assumptions, with the local government effectively addressing community concerns. Consequently, the provision of essential infrastructure, such as Wifi ID, has alleviated signal-related challenges for the residents, showcasing a positive impact on rural development. Highlights: The study investigates challenges in government support for BUMDes in Banjarwungu, emphasizing inadequate infrastructure and local awareness. Employing exploratory methods, the research captures successful BUMDES progress, aligning with goals and assumptions. Results show effective government response, providing essential infrastructure like Wifi ID, positively impacting rural connectivity and development. Keywords: Innovation, BUMDES, Rural Development, Connectivity, Community Engagement.